Public Employment Policies and Regional Unemployment Differences - Vincenzo Caponi (Institute for the Study of Labor (IZA), 2014)
This paper contributes to the existing literature on public employment showing that the wage setting policy of the public sector can be an important determinant of private employment and unemployment. I look at the case of geographically homogeneous wages across regions with different private sector productivity, and show that public employment generates a crowding out effect against private employment. This effect is larger the larger is the public sector share of total employment. I present a two region two sector model based on Pissarides (2000) heterogeneous search and matching model where vacancies are posted by the private and the public sector as in Quadrini and Trigari (2007) and Gomes (2014). I calibrate the model to the Italian labor market and show that the uniform wage setting policy adopted by the central government, in the presence of productivity unbalance across regions, is responsible for up to 40% of the unemployment gap between the North and South. Policy experiments suggest that reducing the size of public employment reduces unemployment in lower productive regions while allowing for regional wage setting in the public sector almost eliminates the unemployment differential.
Keywords: E24; J60; 330; Italy; European unemployment; regional unemployment; public employment